MANFAAT SIMBIOSIS MUTUALISME TERHADAP KEANEKARAGAMAN HAYATI EKOSISTEM HUTAN - Khoirrun Yuridillah Isnaini; Nurmala Siska Dewi; Nurul Hasanah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research is motivated by the importance of understanding the concept of mutualistic symbiosis in forest ecosystems for elementary school students as part of environmentally oriented science learning. Students' lack of understanding of the forms of interaction between living things is a problem that requires a solution through a contextual learning approach. This study aims to analyze the improvement in students' understanding of mutualistic symbiosis through a local ecosystem-based approach. The method used was descriptive qualitative, using observation, interviews, and documentation techniques, applied to fourth-grade students at SDN 057202 Tanjung Jati. The results showed that students were able to more concretely understand the concept of mutually beneficial relationships between living things after implementing forest ecosystem-based learning around the school. The learning process involving the real environment can increase students' active engagement, curiosity, and ecological awareness. Based on these findings, it is recommended that teachers utilize local potential in the learning process to bring students closer to applicable and meaningful scientific concepts. Thus, learning not only focuses on cognitive aspects but also develops character and an attitude of environmental concern.